The impact of obsessive-compulsive personality disorder on obsessive-compulsive disorder: clinical outcomes in the context of bipolarity - Żerdziński, Maciej; Burdzik, Marcin; Dębski, Paweł; Żmuda, Roksana; Piegza, Magdalena; Gorczyca, Piotr (Frontiers in Psychiatry, 2025)
Obsessive-compulsive disorder (OCD) is characterized by obsessions and compulsions that significantly impair functioning. Obsessive-compulsive personality disorder (OCPD) co-occurs in 17-45% of OCD patients, worsening outcomes across multiple domains. Therefore, we aimed to study the impact of OCPD in more detail by analyzing selected comorbidities, emotional aspects, and sociodemographic data. This study assessed 78 OCD patients (average age 44.9 years, 34.61% OCPD), using Y-BOCS, BABS, BPAQ, BIS-11, YMRS, HDRS-17, and ASEX. Patients with comorbid OCPD had significantly worse outcomes in symptom severity (Y-BOCS = 0.0006), treatment duration (p = 0.0127), insight (BABS, p = 0.0185), aggression (p = 0.0266), impulsivity (p = 0.0469), depression (HDRS, p = 0.0178), mania (YMRS, p = 0.0003), and sexual dysfunction (ASEX, p = 0.008). OCPD was more prevalent in unemployed individuals (p = 0.046) and older patients (p = 0.009). No significant differences were found regarding gender, education, or relationship status. Obsessions and compulsions, such as contamination (p = 0.025), somatic (p = 0.018), ruminations (p = 0.003), and obsessional slowness (p = 0.007), were more common in the OCPD group. In the group with OCPD, aggression and OCD severity were correlated with increased levels of depression, which can be considered potential correlates of bipolarity in the relationship between OCD and OCPD. In conclusion, OCPD significantly worsens clinical outcomes in OCD across emotional, behavioral, and functional dimensions.